Phytochemical Characterization and Sensory Evaluation of Vinegar from Melastoma malabathricum L. Flowers with Variations in Starter Concentration and Fermentation Time - Safrida Safrida; Fitrah Asma Ulhusna; Gholib Gholib; Maim Matualiah; Raissya Adinda; Yelly Asmita Putri; Nadila Fitria (Postgraduate, University of Mataram, 2023)
Melastoma malabathricum L. or Senggani is a shrub that is easily found in open meadows.Â Acehnese people often use senggani as traditional medicine. The purpose of this study was to determine the phytochemical content and sensory evaluation of natural vinegar from Senggani flowers. The research design used a completely randomized design (CRD) which consisted of 5 days and 10 days of Saccharomyces administration. Both groups were added with Acetobacter aceti with concentrations of 5%, 10%, and 15% respectively in each sample. The result showed that phytochemical screening Senggani vinegar contains tannins, flavonoids, saponins, dragendrof, polyphenols, and terpenoids. The results of the organoleptic test show that the average ranking of panelists' preference for taste from the combination of the Senggani flower vinegar fermentation treatment ranges from 5.8-6.04, meaning that the taste of vinegar is slightly sour, while the panelists' preference ranking on acceptability ranges from 4.4-5, which means acceptability of panelists is neutral. The Senggani flower vinegar product with added Saccharomyces for 10 days and the fermentation of Acetobacter aceti with concentrations of 15% is the best formula preferred by the panelists. Senggani flower vinegar has the potential to be used as a health drink